Sacubitril/valsartan eligibility and outcomes in the ESC‐EORP‐HFA Heart Failure Long‐Term Registry: bridging between European Medicines Agency/Food and Drug Administration label, the PARADIGM‐HF trial, ESC guidelines, and real world. (18th June 2019) - Kapelios, Chris J.; Lainscak, Mitja; Savarese, Gianluigi; Laroche, Cécile; Seferovic, Petar; Ruschitzka, Frank; Coats, Andrew; Anker, Stefan D.; Crespo‐Leiro, Maria G.; Filippatos, Gerasimos; Piepoli, Massimo F.; Rosano, Giuseppe; et al.
Abstract : Aims: To assess the proportion of patients with heart failure and reduced ejection fraction (HFrEF) who are eligible for sacubitril/valsartan (LCZ696) based on the European Medicines Agency/Food and Drug Administration (EMA/FDA) label, the PARADIGM‐HF trial and the 2016 ESC guidelines, and the association between eligibility and outcomes. Methods and results: Outpatients with HFrEF in the ESC‐EORP‐HFA Long‐Term Heart Failure (HF‐LT) Registry between March 2011 and November 2013 were considered. Criteria for LCZ696 based on EMA/FDA label, PARADIGM‐HF and ESC guidelines were applied. Of 5443 patients, 2197 and 2373 had complete information for trial and guideline eligibility assessment, and 84%, 12% and 12% met EMA/FDA label, PARADIGM‐HF and guideline criteria, respectively. Absent PARADIGM‐HF criteria were low natriuretic peptides (21%), hyperkalemia (4%), hypotension (7%) and sub‐optimal pharmacotherapy (74%); absent Guidelines criteria were LVEF>35% (23%), insufficient NP levels (30%) and sub‐optimal pharmacotherapy (82%); absent label criteria were absence of symptoms (New York Heart Association class I). When a daily requirement of ACEi/ARB ≥ 10 mg enalapril (instead of ≥ 20 mg) was used, eligibility rose from 12% to 28% based on both PARADIGM‐HF and guidelines. One‐year heart failure hospitalization was higher (12% and 17% vs. 12%) and all‐cause mortality lower (5.3% and 6.5% vs. 7.7%) in registry eligible patients compared to the enalapril arm of PARADIGM‐HF. Conclusions: Among outpatients with HFrEF in the ESC‐EORP‐HFA HF‐LT Registry, 84% met label criteria, while only 12% and 28% met PARADIGM‐HF and guideline criteria for LCZ696 if requiring ≥ 20 mg and ≥ 10 mg enalapril, respectively. Registry patients eligible for LCZ696 had greater heart failure hospitalization but lower mortality rates than the PARADIGM‐HF enalapril group.